Evaluation of clinical IMRT treatment planning using the GATE Monte Carlo simulation platform for absolute and relative dose calculations. Issue 2 (18th January 2013) - Benhalouche, S.; Visvikis, D.; Le Maitre, A.; Pradier, O.; Boussion, N.
Abstract : Purpose: : The objective of this study was to evaluate and validate the use of the Geant4 application for emission tomography (GATE) Monte Carlo simulation platform for clinical intensity modulated radiotherapy (IMRT) dosimetry studies. Methods: : The first step consisted of modeling a 6 MV photon beam linear accelerator (LINAC), with its corresponding validation carried out using percent depth dose evaluation, transverse profiles, tissue phantom ratio, and output factor on water phantom. The IMRT evaluation was performed by comparing simulation and measurements in terms of absolute and relative doses using IMRT dedicated quality assurance phantoms considering seven different patient datasets. Results: : Concerning the LINAC simulated model validation tissue phantom ratios at 20 and 10 cm in water TPR 10 20 obtained from GATE and measurements were 0.672 ± 0.063 and 0.675, respectively. In terms of percent depth dose and transverse profiles, error ranges were, respectively: 1.472% ± 0.285% and 4.827% ± 1.323% for field size of 4 × 4, 5 × 5, 10 × 10, 15 × 15, 20 × 20, 25 × 25, 30 × 30, and 40 × 40 cm 2 . Most errors were observed at the edge of radiation fields because of higher dose gradient in these areas. Output factors showed good agreement between simulation and measurements with a maximum error of 1.22%. Finally, for IMRT simulations considering seven patient datasets, GATE provided good results with a relative error of 0.43% ± 0.25% on absolute dose between simulated and measured beams (measurements at the isocenter, volume 0.125 cm 3 ). Planar dose comparisons were also performed using gamma‐index analysis. For the whole set of beams considered the mean gamma‐index value was 0.497 ± 0.152 and 90.8% ± 3.6% of the evaluated dose points satisfied the 5% / 4 mm criterion. Conclusions: : These results show that GATE allows reliable simulation of complex beams in radiotherapy after an accurate LINAC modeling is validated. A simple cross‐calibration procedure proposed in this work allows obtaining absolute dose values even in complex fields.